Psychometric Indicators of the Pro-environmental Attitudes' Questionnaire: Colombian Version - Sierra Barón, Willian; Meneses Baez, Alba Lucia (Frontiers in Psychology, 2022)
The detrimental effect of human behaviour on the environment is undeniable. Attitudes are recognized as a predictor of pro-environmental behaviour; therefore, having good quality tools in Colombia to measure them is strategic to assess interventions. This study aims to establish psychometric indicators for the Pro-Environmental Attitudes Questionnaire (PEAQ) Colombian version to a sample of 415 volunteers (53% women and 47% men) aged 18 to 70 years (M = 40.28; SD = 14.06). We used the 28-item PAQ already linguistically adapted for Colombia. We applied the scales: environmental awareness (EA) (11 items), environmental values (EV) (4 items), and the pro-environmental at work questionnaire (PEWQ) (31 items). We used a one-parameter Rasch model and WINSTEPS program to assess the PEAQ´s one-dimensionality and item statistics by gender, and estimated Spearman's Rho coefficient between the PAQ scores and the scales for convergent validity. The PEAQ in this study has 24 items because 4 items did not fit the Rasch Model criteria. Its one-dimensionality was supported by an explained variance (43%) and the first residual variance (12%). The coefficients α = .95 and Ω = .95; Rasch for persons =.90) and Rasch for items =.95. The correlation between the PEAQ and the EC, EV, and PEWQ scales were Spearman’s Rho = .859 (p≤ .001), .795 (p≤ .001) and .885 (p≤ .001), respectively. Thus, the PEAQ Colombian version’s psychometric indicators support it as a valid and reliable instrument to measure pro-environmental attitudes in this country.